Odpowiedź :
Odpowiedź:
= -14[tex]\frac{1}{3}[/tex] + ( - 6 [tex]\frac{1}{2}[/tex]) + 11 [tex]\frac{5}{6}[/tex] = - 14 [tex]\frac{2}{6}[/tex] + ( - 6 [tex]\frac{3}{6}[/tex] ) + 11 [tex]\frac{5}{6}[/tex] = - 20 [tex]\frac{5}{6}[/tex] + 11 [tex]\frac{5}{6}[/tex] = - 9
= 4 [tex]\frac{2}{10}[/tex] + ( - 5 [tex]\frac{2}{3}[/tex] ) + ( - 2 [tex]\frac{3}{5}[/tex] ) = 4 [tex]\frac{1}{5}[/tex] + ( - 5 [tex]\frac{2}{3}[/tex] ) + ( -2 [tex]\frac{3}{5}[/tex] ) =
= 4 [tex]\frac{3}{15}[/tex] + ( - 5 [tex]\frac{10}{15}[/tex] ) + ( - 2 [tex]\frac{9}{15}[/tex] ) = 4[tex]\frac{3}{15}[/tex] - 7 [tex]\frac{19}{15}[/tex] = 3 [tex]\frac{18}{15}[/tex] - 7 [tex]\frac{19}{15}[/tex] = - 4 [tex]\frac{1}{15}[/tex]
= - 7 [tex]\frac{5}{8}[/tex] + 12 [tex]\frac{3}{4}[/tex] + ( - 5 [tex]\frac{1}{2}[/tex] ) = - 7 [tex]\frac{5}{8}[/tex] + 12 [tex]\frac{6}{8}[/tex] + ( - 5 [tex]\frac{4}{8}[/tex] ) = -12 [tex]\frac{9}{8}[/tex] + 12 [tex]\frac{6}{8}[/tex] = - [tex]\frac{3}{8}[/tex]
Szczegółowe wyjaśnienie: